ANALISIS KEMAMPUAN ADMINISTRASI APARATUR DESA DALAM MENINGKATKAN PELAYANAN PUBLIK DI DESA MENTOR KABUPATEN PROBOLINGGO - Farasandya Amalia Hapsari (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2018)
The purpose of this study was to determine the Administrative Ability of Village Apparatus in Providing Public Services in Mentor Village, Probolinggo Regency. The main problem of this research is How is the Administrative Capability of Village Apparatus in Providing Public Services in Mentor Village, Probolinggo Regency. In this study, researchers looked for data related to the performance of the officials through direct interviews with the community in Mentor Village, Probolinggo Regency. In addition, researchers also collected data from print and electronic media related to the analysis of the ability of officials in Mentor Village, Probolinggo Regency. the activities of the process of selecting, sorting, focusing and simplifying the raw data in all forms of notes and field documents. Activities to reduce data that have been carried out in this study include: recording the results of interviews, observations and documentation both successfully recorded through a recorder and field notes and the results of collecting documents related to the research focus. In this study, the data obtained were then selected and selected, and focused on matters relating to the assessment and performance results of the apparatus of the Mentor Village, Probolinggo Regency. The results showed that the Technical Skill (Technical Ability) of the Mentor Village apparatus carried out their duties using techniques and supporting tools and procedures in accordance with the abilities of a Village official through ONLINE. Human Skill (humane ability) of the Village apparatus of Mentor if viewed from the perspective of the ability of the Village apparatus to motivate each other in carrying out tasks between Village officials is carried out fairly without differentiating social status. Increasing the capacity of Mentor Village officials in the implementation of Village government administration duties which include a) Employee discipline development, b) Education and training, c) Work motivation, d) Career development.